PENGARUH JENIS PREEKLAMPSIA PADA KEHAMILAN TERHADAP LUARAN PERSALINAN PERINATAL DI RSUD BRIGJEND. H. HASAN BASRY KANDANGAN - Rahmadaniyanti, Mutiara; Salmarini, Desilestia Dwi; Hidayah, Nurul Dwi; Yuliana, Fitri Dwi (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2025)
Preeclampsia is a complication of pregnancy and is one of the reasons for the high infani mortality rate. Data for 2022, out of 657 deliveries, 0,03% experienced PE and 0,015% experienced PEB. Perinatal outcome data for pregnant women with preeclampsia, the incidence of BBLR was 38,5%, asphyxia as much as 7,7%; premature as much as 47,9%; and IUFD as much as 2,6%. Identifying and analyzing the effect of preeclampsia in pregnancy on the outcome of perinatal deliveries at RSUD Brigjend. H. Hasan Basry Kandangan in 2022. This type of research used quantitative analysis with a cross sectional approach and a total sampling technique totaling 117 pregnant women who experienced preeclampsia. Results of the 117 pregnant women who had preeclampsia in 2022, it was found that severe preeclampsia PEB) was common in 99 people (84,6%) and preeclampsia (PE) occurred in 18 people (15,4%). The test results onlyaffect the incidence of BBLR with a alue of p value = 0.033 < = 0.05 with 5% there is an effect of preeclampsia. While asphyxia p value = 0.711 > = 0.05; premature p value = 0,208 > = 0.05; and IUFD with a value of p value = 0.454 > = 0.05 there is no effect of preeclampsia. The results showed that there was an effect of the type of preeclampsia in pregnancy had an effect on the incidence of BBLR, while it had no effect the incidence of asphyxia, premature and IUFD at RSUD Brigjend. H. Hasan Basry Kandangan.